The Influence Of Financial Technology, Financial Literacy, And Risk Perception On Mutual Fund Investment Decisions In Generation Z In Jawa Barat: - - Khaera Palesta, Pani; Santi Paramita, V. (International Journal of Science, Technology & Management, 2024)
Generation Z is a generation that grew up in the digital era, where technology and social media have become an important part of their lives. Based on survey results, most of generation Z have expenses that are greater than their income. This shows that they are less wise in financial management and less able to carry out long-term financial planning. On the other hand, current technological advances present various choices and convenience for making financial investments. There are various types of investment products available for short and long term, which have low risk to high risk. For beginner investors, investing in mutual funds is highly recommended. This is because investing in mutual funds in Indonesia can be started with low fund, diversified funds, managed by professional investment management, thereby providing better return opportunities. This research aims to determine the influence of financial technology, financial literacy, and risk perception on generation Z mutual fund investment decisions in West Java. This research method uses quantitative methods with descriptive and associative approaches. The infinite population in this research is Generation Z in West Java who have invested in mutual funds. Respondents have addresses in various cities in West Java. The sample was determined using simple random sampling with a sample size of 80. The results of this study explain that Financial Technology and Risk Perception do not influence Generation Z's mutual fund investment decisions. On the other hand, financial literacy influences Generation Z's mutual fund investment decisions in West Java.